Uso de un esteroide anabolico (Laurato de nandrolona) en la etapa de finalización en porcinos de engorde - Meza Moreira, Yesselia Hellen (2022)
A documentary research was carried out with the objective of generating information on the use of Nandrolona Laurate in the finishing stage in fattening pigs. The Qualitative and Exploratory method will be used in a database with indexed journals, information obtained from DSpace of the universities, bibliographies of academic Google and scientific articles. This bibliographical research allowed to demonstrate that positive effects in the use of the anabolic steroid Laurato de Nandrolona in doses of 1 mg/ Kg. of live weight, with intervals of 30 days, reaching a total of 4 applications during the 120 days in the finishing stage. in fattening pigs they achieve good results in terms of final weight, weight gain being 111.23 and 48.00 Kg. In the same way, the best Feed Conversion with an index of 2.29. Likewise, it is shown that the sows treated with Nandrolona Laurate showed heat for 1654 days, while the pigs without the use of this Anabolic showed heat 2 weeks later. Among the other benefits it has is that it is an anti-stress agent. When used in a trial, the pigs that did not receive doses of Nandrolona Laurate showed stress due to space and temperature, while those that were administered Nandrolona Laurate did not show stress. that phenomenon.